THE EFFECT OF INTUITIVE REFLECTIVE AL-FATIHAH READING TRAINING TOWARDS REDUCING POST-TRAUMA ANXIETY LEVEL IN LOMBOK EARTHQUAKE VICTIMS - Nurwardani, Mayreyna; Julianto, Very; Handayani, Navia Fathona (Psikis : Jurnal Psikologi Islami, 2022)
Al-Fatihah is one of the surahs in the Al-Qur'an that must be memorized by all Muslims. The role of Al-Qur'an, especially Surah Al-Fatihah as a non-pharmacological therapy has begun and widely studied because of the benefits, not only for physical but also psychological health. This study aim to examine the effect of Al-Fatihah reflective intuitive reading training to Post-trauma anxiety level of Lombok’s earthquake victims in 2018. The study using an experimental method with pretest-posttest control group design. Each group consist of 12 adult woman. Post-trauma anxiety level was measured using anxiety sub-test from Depression Anxiety Stress Scale 42 (DASS). The result of Wilcoxon statistical test aim to examine the difference level of anxiety before and after treatment from one group. The result of Wilcoxon analysis showed that Al Fatihah reflective-intuitive reading training could reduce anxiety level significantly after training in experimental group (p = 0.002; p<0.05). Furthermore, Man-Whitney U analysis showed that the difference of anxiety level between control and experiment group (p= 0.001; p<0.05). This study showed that Al Fatihah reflective-intuitive reading training decrease anxiety level of Lombok’s earthquake victims.